Imaging Cu2O nanocube hollowing in solution by quantitative in situ X-ray ptychography - Grote, Lukas; Seyrich, Martin; Döhrmann, Ralph; Harouna-Mayer, Sani Y.; Mancini, Federica; Kaziukenas, Emilis; Fernandez-Cuesta, Irene; Zito, Cecilia A. [UNESP]; Vasylieva, Olga; Wittwer, Felix; Odstrčzil, Michal; Mogos, Natnael; et al. (Springer Nature, 2022)
Understanding morphological changes of nanoparticles in solution is essential to tailor the functionality of devices used in energy generation and storage. However, we lack experimental methods that can visualize these processes in solution, or in electrolyte, and provide three-dimensional information. Here, we show how X-ray ptychography enables in situ nano-imaging of the formation and hollowing of nanoparticles in solution at 155 °C. We simultaneously image the growth of about 100 nanocubes with a spatial resolution of 66 nm. The quantitative phase images give access to the third dimension, allowing to additionally study particle thickness. We reveal that the substrate hinders their out-of-plane growth, thus the nanocubes are in fact nanocuboids. Moreover, we observe that the reduction of Cu2O to Cu triggers the hollowing of the nanocuboids. We critically assess the interaction of X-rays with the liquid sample. Our method enables detailed in-solution imaging for a wide range of reaction conditions.